Colchicine-responsive protracted gouty arthritis with systemic inflammatory reactions. Issue 3 (May 2014) - Nonaka, Fumiaki; Migita, Kiyoshi; Haramura, Tomoko; Sumiyoshi, Remi; Kawakami, Atsushi; Eguchi, Katsumi
Abstract Acute gouty arthritis is a severe but self-limiting arthritis caused by inflammatory responses to urate crystals. Oral colchicines are effective for initial stages or prophylaxis, but generally, colchicines are ineffective for established gouty arthritis. We describe an unusual case of gouty arthritis with systemic inflammatory reactions, including high fever and polymyalgia. Refractory polyarthritis and high fever were eradicated by colchicine treatment. Genetic analysis revealed a heterozygous mutation in exon 2 of the MEFV gene (E148Q). This case underscores the possibility that MEFV gene mutations may modify the phenotype of gouty arthritis.